ANALISIS FAKTOR-FAKTOR FUNDAMENTAL DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Esti Damayanti, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study is to determine and explain the effect of the Quick Ratio and Total Asset Turnover on the Price book Value of Transportation Companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The research method was carried out using Purpose Sampling with a description method and data collection techniques using the documentation method and the Data Analysis Method using Multiple Linear Regression Analysis. From the results of the research that has been done, partially the Quick Ratio and Total Asset Turnover  variables have a significant effect on Price Book Value